Sex and Gender Influence on Cardiovascular Health in Sub-Saharan Africa: Findings from Ghana, Gambia, Mali, Guinea, and Botswana. Issue 1 (1st September 2022) - Dev, Rubee; Favour-Ofili, Divine; Raparelli, Valeria; Behlouli, Hassan; Azizi, Zahra; Kublickiene, Karolina; Kautzky-Willer, Alexandra; Herrero, Maria Trinidad; Pilote, Louise; Norris, Colleen M.
Background: There is an upsurge of cardiovascular diseases (CVDs) in sub-Saharan Africa (SSA). Irrespective of biological sex, gender-related factors could be the precursor of these conditions. Objective: To examine the associations between biological sex, gender-related variables, and cardiovascular health (CVH) risk factors in SSA countries. Methods: We used data from the STEPwise approach to surveillance of risk factors for non-communicable disease survey, conducted in adults from Ghana, Gambia, Mali, Guinea, and Botswana. The main outcome was CVH, measured through the health index with values ranging from 0 (worst) to 5 (best or ideal) CVH. Multivariable logistic regression was applied to determine the gender-related factors related to poorer CVH (index less than 4). Results: Data included 15, 356 adults (61.4% females, mean age 36.9 years). The prevalence of hypertension (21.6% vs. 13.8%) and overweight/obesity (48.3% vs. 27.5%) was higher among females as compared to males. Females were more likely to be unemployed (17.3% vs. 9.7%) or reported unpaid work (36.8% vs. 15.2%). Overall, females showed worse CVH than males (ORfemale = 0.95, 95% CI:0.91–0.99). Being married was associated with better CVH compared with being single, more so for males (ORmale = 1.09, 95% CI:0.96–1.24, pinteraction < 0.01). Males with unpaid work (ORmale = 1.28, 95% CI:1.12–1.47) had better CVH than their unpaid female counterparts (ORfemale = 1.08, 95% CI:1.01–1.17). Conclusion: In SSA populations, being female was associated with poorer CVH given the disproportionate burden of hypertension and overweight/obesity. Gender-related factors such as marital status and unpaid work were associated with better CVH in males compared to females.